Facile synthesis of flower-shaped Au/GdVO4:Eu core/shell nanoparticles by using citrate as stabilizer and complexing agent. Issue 12 (25th January 2016) - Chen, Ming; Wang, Jia-Hong; Luo, Zhi-Jun; Cheng, Zi-Qiang; Zhang, Ya-Fang; Yu, Xue-Feng; Zhou, Li; Wang, Qu-Quan
Abstract : The synthesis of metal/rare-earth core/shell hetero-nanostructures through directly coating rare-earth compound onto the surface of Au nanocrystals. Abstract : Metal/rare-earth core/shell hetero-nanostructures combine the optical properties of metal cores and rare-earth shells, which are widely reported and expected to be used in multitask applications. However, there is still no facile and efficient strategy to directly prepare such materials. Herein, we present a facile hydrothermal method for directly coating rare-earth vanadate shells onto the Au nanoparticle (AuNP) cores. Citrate plays a fascinating and critical role in the whole synthesis process, and not only acts as the capping agent to stabilize the as-prepared AuNP cores and the final products but also serves as the complexing agent to assist the nucleation and growth of rare-earth vanadate shells. Interestingly, the grown Au/GdVO4 :Eu core/shell NPs have a flower-like shape with tunable plasmon resonance and bright fluorescence. The morphology and crystallinity as well as the growth mechanism and tunable optical properties of the Au/GdVO4 :Eu are investigated. The method developed here could be extended for preparing other metal/rare-earth hybrids and the multifunctional products with specific morphology have the potential in the photocatalytic and biomedical application.